2016
DOI: 10.1209/0295-5075/115/41001
|View full text |Cite
|
Sign up to set email alerts
|

Double-slit experiment in momentum space

Abstract: -Young's classic double-slit experiment demonstrates the reality of interference when waves and particles travel simultaneously along two different spatial paths. Here, we propose a double-slit experiment in momentum space, realized in the free-space elastic scattering of vortex electrons. We show that this process proceeds along two paths in momentum space, which are well localized and well separated from each other. For such vortex beams, the (plane-wave) amplitudes along the two paths acquire adjustable pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…So far, only electrons with the modest kinetic energy E k = 300 keV have been produced in electron microscopes [13][14][15]. Second, one needs to achieve sufficiently large transverse momenta of the two colliding particles κ i , which define the size of the transverse momentum ring (12) and the energy range (23) in which all the remarkable phenomena are displayed. Third, one must have sufficient control over the transverse localization of the colliding twisted particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only electrons with the modest kinetic energy E k = 300 keV have been produced in electron microscopes [13][14][15]. Second, one needs to achieve sufficiently large transverse momenta of the two colliding particles κ i , which define the size of the transverse momentum ring (12) and the energy range (23) in which all the remarkable phenomena are displayed. Third, one must have sufficient control over the transverse localization of the colliding twisted particles.…”
Section: Discussionmentioning
confidence: 99%
“…The final particle with mass M is still described in the basis of plane waves, and its momentum K and energy E K satisfy E 2 K = M 2 + K 2 . We follow the procedure of [8,12,23], which adapts the general theory of scattering of non-monochromatic, arbitrarily shaped, partially coherent beams developed in [24] to the collisions of Bessel twisted states, see also the appendix. The S-matrix element of this process is…”
Section: A Pure Bessel Beams: General Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical investigations brought several examples of quantities which have been inaccessible so far, but which could be revealed in vortex-particle collisions [120,121,122,123,124]. In particular, by scattering vortex electrons on a counterpropagating particle and observing the interference fringes in their joint angular distribution, one can directly probe its OAM state [121]. This phenomenon can be employed to probe the proton spin structure.…”
Section: High-energy Perspective: Scattering and Radiationmentioning
confidence: 99%
“…It is shown that the analyses presented here applies equally well to momentum space interference of Ivanov et.al. [27], and the loss of interference in a which-way measurement can be interpreted in terms random position kicks.…”
Section: Momentum Space Interference and Position Kicksmentioning
confidence: 99%